ENTRY-INTERNAL NAVIGATION IN DICTIONARIES: A REVIEW OF THE LITERATURE - Ptasznik, Bartosz (Acta Neophilologica, 2013)
Selecting the correct sense in a polysemous entry may cause difficulty for language learners. Poor dictionary reference skills of users may account for the problems that students encounter in dictionary consultation. In addition, some dictionary users may have a tendency to consult the first sense of an entry and not the remaining senses [Tono 1984], although the information required for understanding the meaning of a word might be situated in the middle or end of an entry. For these reasons, lexicographers have started introducing sense navigation devices in dictionaries: menus and signposts. The main role of these devices is to assist dictionary users in entry consultation by helping them find the right meaning of a word as quickly as possible. The present paper is a review of nine empirical studies [Tono 1992, 1997, 2011; Bogaards 1998; Lew 2010; Lew et al. 2013; Lew and Pajkowska 2007; Lew and Tokarek 2010; Nesi and Tan 2011] focusing on the effectiveness of sense navigation devices in dictionaries. In general, the studies investigate how menus and signposts in dictionary entries affect sense selection accuracy and entry consultation time. Furthermore, observations are made regarding the effect of entry length and proficiency level of users on sense selection accuracy and entry consultation time in the context of menus and signposts. Also, menu and signpost systems are compared.